AB0645 Lymphocyte subsets t, b and nk cells in systemic sclerosis. (15th June 2017) - Schneider, L; Hax, V; Marcondes, N; Xavier, RM; Chakr, R
Abstract : Background: Systemic sclerosis (SSc) is a rare multisystem disease with underlying immune mechanisms, whose pathogenesis remains unclear. Few previous reports have evaluated lymphocyte subpopulations in SSc and your results are conflicting. Objectives: The present study aimed to analyze the lymphocyte subsets in SSc patients in comparison to healthy individuals. Methods: Peripheral blood (PB) samples to analyze lymphocyte subsets were obtained from a non-random convenience sample of 20 SSc patients. Twenty healthy individuals recruited from the blood bank were used as sex and age-matched controls. Blood samples were analyzed by flow cytometry for total T cells, CD4+ and CD8+ T cells subsets, CD19+ B cells and total NK cells. Statistical analyses were performed using the IBM Statistical Package for Social Sciences (SPSS 18.0). Data are expressed as mean ± SD and median and range. Non-parametric Mann–Whitney U test was used for analyses of the flow cytometry. A probability p <0.05 was considered statistically significant. Results: The mean (SD) age of SSc patients was 57.9 (14.2) years, 95% were female and 31.6% presented diffuse cutaneous SSc (dcSSc). Patients presented a lower mean total lymphocyte count compared to healthy controls (23.7% vs. 29.6%, p =0.026) (Table 1 .). No statistically significant differences were found in the percentages or the absolute numbers of T, B or NK cells. Conclusions: Our data support previous reports indicating that depletion of lymphocyte in the PB of SSc patients. However, we found no significant difference in relation to lymphocyte subtypes, which differs from the literature data. References: T and NK Cell Phenotypic Abnormalities in Systemic Sclerosis: a Cohort Study and a Comprehensive Literature Review. Almeida et al, 2015. Liu M, Wu W, Sun X, Yang J, Xu J, Fu W, Li M. New insights into CD4+ T cell abnormalities in systemic sclerosis. Cytokine & Growth Factor Reviews, 2016; 28:31–36. Gambichler T, Tigges C, Burkert B, Höxtermann S, Altmeyer P, Kreuter A. Absolute count of T and B lymphocyte subsets is decreased in systemic sclerosis. Eur J Med Res 2010; 15:44–46. Disclosure of Interest: None declared